Degenerative changes of the thoracic spine do exist in patients with diffuse idiopathic skeletal hyperostosis: a detailed thoracic spine CT analysis. (November 2018) - Slonimsky, Einat; Lidar, Merav; Stern, Myriam; Eshed, Iris
Background: Degenerative intervertebral disease (DID) is an exclusion criterion in the Resnick and Niwayama radiographic classification for diffuse idiopathic skeletal hyperostosis (DISH). However, although DID was previously described in DISH, no systematic computed tomography (CT) analysis has been reported so far. Purpose: To assess for the presence and prevalence of such changes on CT examinations of the thoracic spine of individuals with DISH. Material and Methods: Intervertebral space (D1–L1) on chest CT examinations of DISH patients was retrospectively evaluated for the presence of DID. Parameters evaluated were disc space height, disc protrusion, subchondral cysts/sclerosis, Schmorl nodes, vacuum phenomenon, and posterior elements including costovertebral and facet joints. Parameters were compared with two age- and gender-matched control groups of individuals whose entire spine CT lacked evidence of DISH (Control 1 individuals < 2 flowing osteophytes, Control 2 individuals < 4 and ≥ 2 flowing osteophytes). Results: A total of 158 participants (DISH/Control 1/Control 2 = 54/54/50; 106 men, 52 women; average age = 70.6 years) were evaluated. Average intervertebral disc height was significantly lower in the DISH group compared with both control groups (DISH/Control 1/Control 2 = 4.55/5.13/5.01 mm, P < 0.001). Costovertebral degenerative changes were more prevalent in DISH patients ( P < 0.05) and, except for vacuum phenomenon (more prevalent in controls), other DID changes were as prevalent in DISH as in controls. Conclusion: The presence of degenerative intervertebral changes on thoracic CT should not deter from diagnosing DISH. Thus, the radiographic Resnick and Niwayama DISH criteria cannot be directly adapted to CT.